The Puritan experiment : New England society from Bradford to Edwards - Bremer, Francis J. (University Press of New England, 1995)
The comprehensive history of a system of faith that shaped the nation.
Keywords: Puritans -- New England.; New England -- History -- Colonial period, ca. 1600-1775.; Puritains -- Nouvelle-Angleterre.; Nouvelle-Angleterre -- Histoire -- ca 1600-1775 (Période coloniale); HISTORY -- State & Local.; HISTORY -- State & Local -- General.; HISTORY / General; Puritans; New England; Puritanismus; Neuengland; Puritanisme.; 1600-1775; History